Bromotryptophans and their incorporation in cyclic and bicyclic privileged peptides. Issue 10 (12th March 2018) - García‐Pindado, Júlia; Willemse, Tom; Goss, Rebecca; Maes, Bert U. W.; Giralt, Ernest; Ballet, Steven; Teixidó, Meritxell
Abstract: While revisiting biologically active natural peptides, the importance of the tryptophan residue became clear. In this article, the incorporation of this amino acid, brominated at different positions of the indole ring, into cyclic peptides was successfully achieved. These products demonstrated improved properties in terms of passive diffusion, permeability across membranes, biostability in human serum and cytotoxicity. Moreover, these brominated tryptophans at positions 5, 6, or 7 proved to be compatible as building blocks to prepare bicyclic stapled peptides by performing on‐resin Suzuki‐Miyaura cross‐coupling reactions. Abstract :